مساهمة في تطوير نموذج تقويم مخاطر صناعة التشييد على الصحة والسلامة المهنية - حالة دراسة (المنطقة الساحلية في سوريا) - شاهين هيثم; شيبان سامية; نيوف هزار (Latakia University Journal -Engineering Sciences Series, 2019)
The assessment of occupational health and safety in construction projects is a complex process involving many random variables that are difficult to be quantified. This research presents a model based on fuzzy logic to assess the risk of health and safety occupational in construction. The model was applied in construction projects in the coastal area and contribution in improving an effective structure in managing these risks. From field study and literature review, six main risks are determined in construction industry. To determine each risk, a survey was designed and distributed in two construction locations, in addition to observation, and then treating the lexical variables in the survey to obtain the risk matrix using the fuzzy logic. The value of each risk is evaluated basing on four factors Safety Climate, Severity, Possibility and Safety Barriers. The results showed a low safety climate in the studied locations. The simulations showed that the synergistic effect of periodic training of workers in addition to inexpensive efficient safety barriers can reduce the mentioned risks by the half approximately. يُعتبَر تقدير الصحة والسلامة المهنية ضمن مشاريع البناء عملية معقدة تتضمن الكثير من المتغيرات العشوائية التي من الصعب أن نحيط بها كميّاً. يعرض البحث نموذجاً يعتمد على المنطق الضبابي ويهدف إلى تقييم خطر الصحة والسلامة المهنية في عمليات التشييد. تم تطبيق النموذج على عمليات التشييد في المنطقة الساحلية والمساهمة في تطوير هيكلية فعالة في إدارة هذه المخاطر. من خلال الدراسة الميدانية والمرجعية تم حصر ستة مخاطر أساسية يتعرض لها فريق العمل في صناعة التشييد. حيث يتم قياس مقدار كل خطر اعتماداً على أربعة عوامل هي مناخ السلامة العام, شدة هذا الخطر، احتمال حدوثه وفاعلية حواجز السلامة التي تم استنتاجها عن طريق استبيان الخبراء ومن ثم معالجته بالمنطق الضبابي وذلك في موقعين قيد الإنشاء للحصول على مصفوفة الخطر. أظهرت النتائج تدني المناخ العام للسلامة في مواقع الدراسة. أظهرت عمليات المحاكاة أن التأثير المتضافر للتدريب الدوري للعمال بالإضافة إلى حواجز سلامة فعالة غير مكلفة من شأنه تقليل المخاطر المذكورة بمقدار النصف تقريباً.